2010
DOI: 10.1073/pnas.1010836107
|View full text |Cite
|
Sign up to set email alerts
|

Scaling expectations for the time to establishment of complex adaptations

Abstract: Although the vast majority of research in evolutionary biology is focused on adaption, a general theory for the population-genetic mechanisms by which complex adaptations are acquired remains to be developed. The issue explored here is the procurement of novel traits that specifically require multiple mutations to achieve a fitness advantage. By highlighting the roles played by the forces of mutation, recombination, and random genetic drift, and drawing from observations on the joint constraints on these facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 47 publications
2
59
0
Order By: Relevance
“…The mean waiting time until a male-beneficial duplicate becomes established by either process is T ¼ 1/(1/T drift 1 1/T res ) (see Weinreich and Chao 2005;Lynch 2010;Lynch and Abegg 2010), which is negatively correlated with the population size (N e ), the proportion of male-beneficial relative to null mutations (u b /u n ), and the strength of selection in males (s m ; Figure 1a; supporting information, Figure S1). Each parameterization set yields a long waiting time until duplicate invasion.…”
Section: Invasionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean waiting time until a male-beneficial duplicate becomes established by either process is T ¼ 1/(1/T drift 1 1/T res ) (see Weinreich and Chao 2005;Lynch 2010;Lynch and Abegg 2010), which is negatively correlated with the population size (N e ), the proportion of male-beneficial relative to null mutations (u b /u n ), and the strength of selection in males (s m ; Figure 1a; supporting information, Figure S1). Each parameterization set yields a long waiting time until duplicate invasion.…”
Section: Invasionmentioning
confidence: 99%
“…This represents a special case of ''stochastic tunneling'' (Komarova et al 2003). Modifying the results of several previous studies (Iwasa et al 2004;Weissman et al 2009;Lynch 2010;Lynch and Abegg 2010), the mean waiting time until a male-beneficial duplicate becomes fixed by the tunneling process is…”
Section: Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were concerned with computing fixation times of the advantageous type 2 cells and rely on the assumption that the number of type 1 cells is small. Finally, the horizontal striped region approximately corresponds to the literature of crossing fitness valleys, notably Weinreich and Chao (2005), Weissman et al (2009), Lynch (2010, and Altland et al (2011). These studies are concerned with 1=N , r 2 2 r 0 ( 1.…”
Section: Resultsmentioning
confidence: 99%
“…Using this process, Weinreich and Chao (2005) determined the critical population sizes for sequential fixation or stochastic tunneling, and Weissman et al (2009) calculated the rate of tunneling as a function of the mutation rates, population size, and relative fitness of cells harboring one mutation. Finally, these results were extended to investigate the effects of recombination, or sexual reproduction, on the rate of stochastic tunneling (Weissman et al 2010;Lynch 2010;Altland et al 2011). These authors found that the time to establishment of the double-mutant cells can be reduced by several orders of magnitude when sexual reproduction is considered (Weissman et al 2010).…”
mentioning
confidence: 99%